2019
DOI: 10.1080/23322039.2019.1567965
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and cognitive reflection across gender and nationality the case of the United Arab Emirates

Abstract: This study aims to investigate the effect of gender differences and nationality on the Cognitive Reflection Test (CRT), as well as behavioural biases. A sample of 770 questionnaires was collected from undergraduate business students in public and private universities across the United Arab Emirates. The results suggested that low CRT values were dominant in males and females alike for non-UAE citizens in the age group of 18-22 years old, of whom at least one of the parents had a college degree. Subjects with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…These participants fall in the category of 'non-reflectors'; participants can summarise and describe the concepts, but they lack the assessment of their learning (Kember et al, 1999). In support of this finding, Mallek et al (2019) showed that female Emirati students scored lower than their male counterparts in the Cognitive Reflection Test (CRT). In another study, international students from high-power distance cultures found it difficult to reflect critically in writing or challenge the reading materials or instructors (Varner & Peck, 2003).…”
Section: Challenges With Reflective Journalsmentioning
confidence: 91%
“…These participants fall in the category of 'non-reflectors'; participants can summarise and describe the concepts, but they lack the assessment of their learning (Kember et al, 1999). In support of this finding, Mallek et al (2019) showed that female Emirati students scored lower than their male counterparts in the Cognitive Reflection Test (CRT). In another study, international students from high-power distance cultures found it difficult to reflect critically in writing or challenge the reading materials or instructors (Varner & Peck, 2003).…”
Section: Challenges With Reflective Journalsmentioning
confidence: 91%